Understanding Human Behavior in Finance: A Qualitative Study on Cognitive Biases and Decision-making in Investment Practices - Noch, Muhammad Yamin; Rumasukun, Mohammad Ridwan (Golden Ratio of Finance Management, 2024)
This qualitative research delves into cognitive biases and decision-making in investment practices to comprehend the intricate dynamics shaping human behavior in financial markets. The study aims to explore the influence of cognitive biases, emotional factors, and socio-cultural influences on investment decisions. Adopting thematic analysis, relevant literature on cognitive biases and decision-making in investment practices is systematically reviewed. The data analysis process involves iterative coding to identify recurring themes and patterns. Findings reveal the pervasive impact of cognitive biases such as overconfidence and confirmation bias on investment behavior, leading to suboptimal decision-making outcomes. Emotional factors like fear of missing out (FOMO) drive speculative behavior among investors, contributing to market inefficiencies. Moreover, socio-cultural factors influence risk perception and decision-making norms, shaping investment strategies across different cultural contexts. The study underscores the importance of recognizing and addressing cognitive biases in investment practices to improve decision outcomes and enhance long-term financial well-being. Behavioral interventions and technological advancements offer promising avenues for mitigating cognitive biases and enhancing decision-making efficiency. The implications for future research include deeper exploration of underlying mechanisms driving biases and cross-cultural comparisons to inform culturally sensitive interventions. This study contributes to advancing knowledge in behavioral finance and informs evidence-based practices in investment management.